Penerapan Prinsip Restoratif Justice terhadap Pertimbangan Hakim Dalam Putusan Lepas dari segala Tuntutan Hukum( studi Kasus Putusan Nomor: 28/Pid.B/2022/PN.LBB) - Immanuel Rich, Johannes; Djaja, Benny (LPPM Universitas Ekasakti Padang, 2024)
The application of restorative justice in a criminal case must involve coordination from all levels of law enforcement agencies. Theft is an action that falls into the criminal category where the perpetrator of the theft takes property belonging to another person illegally without the owner's permission. Of course, this act of theft harms one party, namely the victim. At this time, many thefts are found to occur within the environment, not far from those close to the environment itself, it is not uncommon for theft to be carried out by those closest to us. Basically, every person who commits theft must be proven to have fulfilled all the elements of a criminal act as stated in the formulation of Article 362 of the Criminal Code, stealing here is defined as taking something that wholly or partly belongs to another person with the intention of possessing it unlawfully, punishable by a maximum sentence of five years. prison and fine... As for the Problem Formulation: 1. How are the Principles of Restorative Justice Applied to Judges' Considerations in Decisions to Release All Legal Claims (Case Study Decision Number: 28/Pid.B/2022/PN.LBB)? and 2. What are the obstacles in applying the principles of restorative justice to the judge's considerations in making a decision to release all legal claims? The conclusions of this research are: 1. The panel of judges who handled the cases in this research were not guided by the Decree of the Director General of the General Justice Agency Number: 1691/DJU/SK/PS.00/12/2020 concerning guidelines for implementing restorative justice in the General Court environment .The defendant Dedi's case does not meet the requirements for restorative justice as stipulated in National Police Regulation no. 8 of 2021 concerning Handling Criminal Acts Based on Restorative Justice and Attorney General Regulation no. 15 of 2020 concerning Termination of Prosecution based on Restorative Justice and does not fulfill legal objectives, namely the principles of legal certainty, justice and expediency and conclusion 2. The implementation of the concept of restorative justice in the integrated criminal justice system in Indonesia has not been implemented in an integrated manner with the absence of high-level regulations regarding implementation of restorative justice, including clear technical instructions with the aim of ensuring that the perpetrator truly recovers and is accepted back into society. This is why the criminal justice sub-systems (police, prosecutor's office, judiciary, correctional institutions) in Indonesia do not fully understand what is actually meant by the concept of restorative justice.